أثر استخدام تكنولوجيا المعلومات على أداء طلبة جامعة تشرين باستخدام التحليل التمييزي - أحمد, طالب (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت هذه الدراسة لمعرفة أثر استخدام تكنولوجيا المعلومات على أداء الطلبة في كليات جامعة تشرين, ومعرفة أياً من عوامل استخدام تكنولوجيا المعلومات التي ساهمت في حدوث التفاوت والاختلاف بين أداء الطلبة, وإيجاد نموذج رياضي لتصنيف أداء الطلبة من خلال استخدام أسلوب التحليل التمييزي. وكانت أهم النتائج التي تم التوصل إليها هي: وجود تأثير لمتغيرات المصادر والمراجع العلمية, مخابر الحاسوب, الانترنت, فهم المواد الحاسوبية, المدرسين المختصين على تصنيف أداء الطلبة, وعدم وجود تأثير لمتغيرات: إتقان اللغة الاجنبية, توفر أجهزة العرض على تصنيف أداء الطلبة.كذلك تم الحصول على ثلاث دوال تمييزية تعكس أداء الطلبة, تبين أيضاً أن النموذج المقترح صنف أفراد العينة المدروسة تصنيفاً صحيحاً بنسبة70.2 %, حيث يوجد أثر معنوي للنموذج المقترح على تصنيف أداء الطلاب. This study aimed at identifying the impact of information technology use on the student's performance amongst Tishreen University faculties, and identifying which factors relate to information technology use have contributed to the differences and variations in student's performance. Consequently, developing a mathematical model for classifying students' performance using discriminant analysis.The most important findings of this research are: There is a significant classification impact of the availability of the following factors: sources and scientific references, computing laboratories, the Internet, computing curriculum, tutors followed training courses in student's performance classification. The findings showed that there is no significant classification impact of the following two factors: foreign language proficiency and the availability of data show facilities on the student's performance classification.In addition, three discriminant functions are obtained which reflect student's performance. Furthermore, the developed model classified studied sample members correctly with 70.2%, which reflect a significant impact of the developed model on classifying student's performance.